Analisis Kekuatan Struktur Beton Bertulang Menggunakan Material Tambahan Abu Terbang (Fly Ash) - Ahmad Nurhadi (Journal of Engineering and Technological Science, 2025)
This study investigates the structural strength of reinforced concrete incorporating fly ash as a supplementary material. Fly ash, a byproduct of coal combustion in power plants, has pozzolanic properties that can enhance the performance of concrete. The primary aim is to evaluate the mechanical properties and durability of reinforced concrete when partially replacing Portland cement with varying percentages of fly ash. An experimental approach was used, involving compressive strength testing, flexural strength analysis, and durability assessments over different curing periods. The results indicate that fly ash improves long-term strength and sustainability while reducing cement usage. The optimum fly ash content observed was 20%, which demonstrated a balance between strength gain and environmental benefits. These findings suggest that fly ash is a viable alternative material in reinforced concrete construction for improving structural performance and sustainability.